Perancangan Branding Kre Sesek Sentra Tenun “Karya Mandiri” Sumbawa melalui Media Desain Komunikasi Visual - Abdurrozaq, Abdurrozaq; Rahma Deni, Gustu (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This research was motivated by the condition of the weaving craftsmen at the “Karya Mandiri” Weaving Center Sumbawa who had difficulty in marketing the woven fabric products they produced, Kre Sesek (traditional woven cloth typical of Sumbawa). This study aims to design the branding of Kre Sesek Sentra Weaving “Karya Mandiri” Sumbawa to be better known by the wider community through the use of visual communication media. The research method used is a qualitative research method with a case study approach. Methods of collecting data through observation, literature study, interviews, and documentation. The research data obtained, then analyzed in order to develop the right branding concept. The branding concept used is KRESAMAWA (Kre Sesek Samawa)